2020
DOI: 10.3389/fpsyg.2020.555576
|View full text |Cite
|
Sign up to set email alerts
|

Trail Pheromone Does Not Modulate Subjective Reward Evaluation in Lasius niger Ants

Abstract: Comparing the value of options is at the heart of economic decision-making. While an option may have an absolute quality (e.g. a food source has a fixed energy content), the perceived value of the option may be malleable. The factors affecting the perceived value of an option may thus strongly influence which option is ultimately chosen. Expectations have been shown to be a strong driver of perceived value in both humans and social insects, causing an undervaluation of a given option if a better option was exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 90 publications
1
3
1
Order By: Relevance
“…In a study conducted in parallel to our work (Oberhauser et al, 2020), the presence of pheromone trails leading to a sucrose solution did not influence food acceptance or feeding behavior of Lasius niger ants, a result that, in principle, contradicts our findings. These ants had to run once on a 20-cm channel covered with filter paper, onto which different amounts of trail pheromone were applied.…”
Section: Glmm (B)contrasting
confidence: 89%
See 1 more Smart Citation
“…In a study conducted in parallel to our work (Oberhauser et al, 2020), the presence of pheromone trails leading to a sucrose solution did not influence food acceptance or feeding behavior of Lasius niger ants, a result that, in principle, contradicts our findings. These ants had to run once on a 20-cm channel covered with filter paper, onto which different amounts of trail pheromone were applied.…”
Section: Glmm (B)contrasting
confidence: 89%
“…Important differences between this work and ours are the duration and method chosen for pheromone exposure. Whereas in our work, Argentine ants were pre-exposed for 20 min in an enclosure before they departed to the food source, in Oberhauser et al (2020), L. niger ants were not pre-exposed to the pheromone, but exposed during a single short run in the channel. This means that their experience with the pheromone was significantly shorter than that of the Argentine ants in our work.…”
Section: Glmm (B)mentioning
confidence: 90%
“…Unlike the serial position, pheromone did not significantly affect the choices of ants in our study. This suggests that the presence of pheromone does not alter learning in a systematic way, which is in accordance with other studies which found no effect of pheromone on learning in Linepithema humile ( Rossi et al, 2020 ) or Lasius niger ( Oberhauser et al, 2020b ; Czaczkes et al, 2016 , but see Czaczkes et al, 2013a ). At a collective level, such independent evaluation of a food source by multiple ants (conditioned amplification: Feinerman and Korman, 2017 ) is crucial for keeping positive feedback in check and preventing collective biases during decision making.…”
Section: Discussionsupporting
confidence: 92%
“…In honeybees, geraniol, an attractive pheromone, improved olfactory associative learning, while 2-heptanone, an aversive pheromone, impaired learning ( Baracchi et al, 2020 ). Evidence for the effect of trail pheromones on ant learning is, however, mixed ( Czaczkes et al, 2016 , 2013a ), and their impact on foraging ants might be species specific ( Oberhauser et al, 2020b ; Rossi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pheromones do more than conveying specific messages to members of the same species. In insects, for instance, they can modulate in the long term responsiveness to relevant stimuli (appetitive, aversive) in contexts that differ from the one for which the pheromone is used as a messenger (Baracchi et al 2017;Rossi et al 2018;Hostachy et al 2019;Rossi et al 2019;Baracchi et al 2020;Murmu et al 2020;Oberhauser et al 2020;Rossi et al 2020). Further studies are needed to clarify these novel functions of pheromones as neuromodulators and to understand their implications for the functioning of recognition systems in general.…”
Section: Discussionmentioning
confidence: 99%